CHCHD10 variant p.(Gly66Val) causes axonal Charcot-Marie-Tooth disease - Auranen, Mari (Neurol Genet, 2015)
OBJECTIVE: We describe the phenotype consistent with axonal Charcot-Marie-Tooth disease type 2 (CMT2) in 4 families with a c.197G>T (p.(Gly66Val)) variant in CHCHD10. METHODS: We sequenced the CHCHD10 gene in a cohort of 107 families with CMT2 of unknown etiology. The patients were characterized by clinical examination and electroneuromyography. Muscle MRI and biopsy of the muscle or nerve were performed in selected cases. Neuropathologic autopsy was performed in 1 case. RESULTS: The c.197G>T variant in CHCHD10 was found in 6 families, 4 of which included multiple individuals available for detailed clinical study. Variants in this gene have recently been associated with amyotrophic lateral sclerosis-frontotemporal dementia, mitochondrial myopathy, or spinal muscular atrophy Jokela type (SMAJ), but not with CMT2. Our patients had a late-onset distal axonal neuropathy with motor predominance, progressing to involve sensory nerves. Neurophysiologic and neuropathologic studies confirmed the diagnosis of sensorimotor axonal neuropathy with no loss of anterior horn neurons. Muscle biopsies showed occasional cytochrome c oxidase–negative fibers, combined with small amounts of mitochondrial DNA deletions. CONCLUSIONS: CHCHD10 c.197G>T (p.(Gly66Val)) is a cause of sensorimotor axonal neuropathy. This gene should be considered in patients presenting with a pure CMT2 phenotype, particularly when motor symptoms predominate.